2015
DOI: 10.1016/j.jbspin.2015.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular injections in thumb osteoarthritis: A systematic review and meta-analysis of randomized controlled trials

Abstract: This meta-analysis shows great heterogeneity. Hyaluronic acid may be useful to increase functional capacity and corticosteroids to decrease pain in thumb osteoarthritis at week 24.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 25 publications
1
30
0
3
Order By: Relevance
“…A slightly different position in terms of applying HA is presented by the ACR, whose guidelines do not recommend applying HA and corticosteroids in OA of MCP joints due to the insufficient amount of evidence proving effectiveness of these specimens [65]. Some of the research highlights the wider importance of HA in improving the functionality of affected joints and the more significant role of CST in reducing pain [66]. It should be noted that at the moment there are no studies showing the significance of acid injection with different molecular weights in the discussed joint [67].…”
Section: The Role Of Hyaluronic Acid In Degenerative Arthritis Treatmentmentioning
confidence: 99%
“…A slightly different position in terms of applying HA is presented by the ACR, whose guidelines do not recommend applying HA and corticosteroids in OA of MCP joints due to the insufficient amount of evidence proving effectiveness of these specimens [65]. Some of the research highlights the wider importance of HA in improving the functionality of affected joints and the more significant role of CST in reducing pain [66]. It should be noted that at the moment there are no studies showing the significance of acid injection with different molecular weights in the discussed joint [67].…”
Section: The Role Of Hyaluronic Acid In Degenerative Arthritis Treatmentmentioning
confidence: 99%
“…Despite the prevalence of thumb carpometacarpal osteoarthritis (TCMC-OA), there is a distinct lack of robust clinical effectiveness studies into conservative interventions on this condition. Recent systematic reviews for the management of TCMC-OA have identified a notable paucity of clinical trials to guide recommendations for clinicians treating this disease and underlined a pressing need for well-designed studies to promote new therapeutic choices (Bertozzi et al, 2015;Hamasaki et al, 2015;Trellu, Dadoun, Berenbaum, Fautrel, & Gossec, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The same review found evidence that hand exercises might improve grip strength and hand function; however, evidence was based on individual trials using different exercise programmes. With regard to pharmacological management, there are insufficient data available to support the efficacy of intra-articular therapy with either corticosteroids or hyaluronic acid15 and their use is not recommended by the 2012 American College of Rheumatology (ACR) guidelines 16. On the other hand, non-steroidal anti-inflammatory drugs (NSAIDs) are recommended to relieve pain associated with thumb base OA, and topical formulations are recommended over oral NSAIDs in the most recent guidelines, due to a superior safety profile 16–18.…”
Section: Introductionmentioning
confidence: 99%